Attitudes towards the mandatory arrest response to domestic battering: gender and institutional differences from a traditional and a women's university - Perrott, Stephen B. (Legal and criminological psychology, 1997)
Although a mandatory arrest response to all instances of domestic assault has been increasingly adopted by the criminal justice systems in both Canada and the US, little is yet known about the extent of support for this policy or the belief system which would underlie support. In an exploratory investigation of attitudes related to this policy, 271 Canadian undergraduates were surveyed both from a fairly typical institution and a predominantly women's university. Results showed women to be more supportive of mandatory arrest than men, with this gender difference more pronounced for students from the women's university. The belief system associated with support for this initiative was largely independent of attitudinal measures of authoritarianism, just world beliefs, and pro-feminist sentiment. Inconsistent with the ideology of domestic violence reform was the finding that both men and women considered situational variables when considering an appropriate institutional response to battering. Results are discussed both in relation to differing levels of political awareness and more fundamental experiential differences between men and women.